Filiation and the protection of parentless children (Malaysia) - Mohd, Azizah (T.M.C. Asser Press (Springer), 2019)
Filiation (nasab) under Islamic law generally refers to lineage or descent from a marriage relationship, be it maternal or paternal. Nevertheless, a mere maternal lineage without mar-riage may not confer nasab to a child. Therefore, paternal lineage is very significant in a child’s life as it safeguards the status conferred upon the child through its father within a family. Adoption, on the other hand, can be understood as taking the child of another into a person’s custody and care as one’s own child. Adoption thus changes the status of the child from the child of one person to the child of another person and confers nasab to the child through the child’s adoptive father, or parent. In Islam, this kind of adoption is known as ‘tabanni’ and is prohibited. On the other hand, Islamic law recognizes and encourages foster parenting so as to provide help and assistance to children in need of protection, without affecting the status of the child. In this spirit, adoption law in Malaysia was enacted with the aim of catering to a multiracial society and taking into account both religious and cultural limitations. Thus, in Malaysia the law on adoption is regulated in two Acts: (i) the Registra-tion of Adoptions Act 1952, governing both Muslims and non-Muslims and (ii) the Adop-tion Act 1952, governing only non-Muslims. This paper explores the practice and law of filiation and adoption as governing Muslims in Malaysia. It examines the legal provisions and seeks to assess whether the law provides for a balanced approach in line with Islamic law while at the same time providing means and alternatives for child protection especially for parentless children.